Past, Present, Future: The Historical Evolution of Metropolitan Planning Conceptions and Styles. - Galland, Daniel; Tewdwr-Jones, Mark (Springer, 2020)
This chapter examines the historical evolution and emerging trends and priorities of metropolitan planning through an analysis concerning its substance and processes. The point of departure is an analysis of the evolving driving forces that influence the adoption and articulation of different planning conceptions and planning styles in catering to metropolitan development. The aim is to periodise substantive and procedural debates pertaining to change and continuity of the institution of planning in its task to shape metropolitan regions. Emphasis is placed on European casuistry, but we also allude to metropolitan planning efforts undertaken elsewhere. On this basis, we illustrate how different spatial ideas relate to evolving development orientations, and how particular planning rationales reflect key values and preferences shaping the roles of planning and their agents.
Keywords: Metropolregion; Planungsansatz; Planungsgeschichte; Planungsprozess; Einflussfaktor; Regionalentwicklung; Globalisierung; Internationaler Vergleich; Finanzialisierung